Optimization of Coconut Fiber in Coconut Shell Concrete and Its Mechanical and Bond Properties - Anandh Sekar (Materials, 2018)
Coconut shell concrete is one of the recently established lightweight concretes. This paper discusses the optimization of adding coconut fibers in both coconut shell concrete and conventional concrete. Coconut fibers at different aspect ratios of 16.67, 33.33, 50, 66.67, 83.33, and 100 and volume fractions of 1, 2, 3, 4, and 5% were tried. The maximum compressive strength was attained at an aspect ratio of 83.33 and volume fraction of 3% for conventional concrete, and aspect ratio 66.67 and volume fraction 3% for coconut shell concrete. Flexural strength increased by 30.63% (conventional concrete) and 53.66% (coconut shell concrete) on the addition of coconut fibers. Similarly, the split tensile strength increased by 19.44% and 30%, respectively. The number of blows needed for failure of specimen in impact resistance test was more for concrete mixed with fibers. The experimental bond stresses were higher than the theoretical values recommended by IS 456: 2000 (Indian Standard) and BS 8110 (British Standard). This study shows that the addition of coconut fiber enhances the properties of both conventional and coconut shell concrete.